1994
DOI: 10.1111/j.1365-2362.1994.tb01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of vitamins C and E on the oxygen free radical production in human polymorphonuclear leucocytes

Abstract: Beneficial effects of dietary supplementation with antioxidant vitamins are attributed mainly to the influence upon lipid metabolism, endothelial and vascular functions. Their effect upon leucocyte oxygen free radical producing capacity has not been investigated. In 13 healthy volunteers we examined the influence of oral supplementation with vitamins C and E (aa 600 mg per day for 14 days) upon leucocyte oxygen free radical production estimated by lucigenin-amplified chemiluminescence in isolated leucocytes st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In another study [9], ·-tocopherol supplementation for 3 months failed to exert any significant effect on either whole blood CL or migration of the patients' neutrophils. On the other hand, a decrease in the CL has also been reported in isolated leukocytes after oral supplementation with vitamin E in volunteers [10]. A transient inhibition of the PMAactivated luminol CL during administration of vitamin E was shown in another study [11].…”
Section: Discussionmentioning
confidence: 88%
“…In another study [9], ·-tocopherol supplementation for 3 months failed to exert any significant effect on either whole blood CL or migration of the patients' neutrophils. On the other hand, a decrease in the CL has also been reported in isolated leukocytes after oral supplementation with vitamin E in volunteers [10]. A transient inhibition of the PMAactivated luminol CL during administration of vitamin E was shown in another study [11].…”
Section: Discussionmentioning
confidence: 88%
“…Still, Kearns et al [29] documented that pretreatment with oral vitamin C relieves endothelial injury against acute muscle I/R injury as an antioxidant agent possibly by attenuating neutrophil respiratory burst activity. Herbaczynska-Cedro et al [30] demonstrated that vitamin C reduces oxygen free radicals production in human circulating neutrophils. For this reason, we included vitamin C to compare with iloprost effect in this study.…”
Section: Discussionmentioning
confidence: 98%
“…11 It decreases both the generation of oxygen free radicals by neutrophils and subsequent lipid peroxidation. 9,34,35 The systemic nature of the activity of vitamin C is shown by the reduction in circulating neutrophil respiratory burst after five days of oral treatment. By lowering the proinflammatory activity of neutrophils distant to the site of injury, pretreatment with vitamin C may decrease subsequent tissue damage when these neutrophils are chemoattracted to the site of IRI.…”
Section: Discussionmentioning
confidence: 99%